Earnings Persistence and Firm Performance: Implications for Analysts’ Accurate Forecast Ability from the Emerging Market of Nigeria - Theophilus Anaekenwa Aguguom; Samuel, O. Dada; Appolos, N. Nwaobia (Modern Perspectives in Economics, Business and Management Vol. 6, 2021)
This paper examined the potency and value relevance of earnings persistence and its effect on firm performance, implications of the analysts’ accurate forecast ability from the emerging market of Nigeria. The study adopted ex-post facto research design and sampled 51 companies listed on the Nigerian Stock Exchange using stratified random sampling technique, covering a period of 11 years 2009-2019. Descriptive statistics and Panel data regression analysis were employed to analyze the effect of earnings persistence on firm performance. Diagnostic Tests were carried out: Variance Inflation Factor showed no evidence of multi-collinearity among the variables, Correlation Matrix test did not revealed any multicollinearity problem, normality test using Jarque-Bera test of normality posed no problem to the study. While Breusch–Pagan/Cook–Wesberg test to assess the variance in the error terms (residuals) of the models, the results indicated that all the models did not suffer from heteroscedasticity. The study revealed that EPERS had a negative and no significant effect on firm performance (Tobin’s Q). Leverage exhibited a positive relationship whereas firm size revealed a negative relationship with Tobin’s Q (TQ). Also based on findings, a weak growth trend was established between EPERS and Tobin’s Q. Earnings persistence resulting from discretionary and opportunistic earnings could give inaccurate forecasting ability. Consequently, the study recommended that analysts should be watchful of the stability of earnings when evaluating reported financial statements, without which, predictions made from them could have negative and misleading implications.